1/4(2x-12)=2/3(3x+9)
1/4(2x-12)=2/3(3x+9) 0.5x - 3 = 2(x+3) 0.5x - 3 = 2x+6 -3-6 = 2x-0.5x 1.5x = -9 x = -9/1.5 x = -6 .
Question
Updated 12/22/2014 2:13:51 AM
Rating
3
1/4(2x-12)=2/3(3x+9)

0.5x - 3 = 2(x+3)

0.5x - 3 = 2x+6

-3-6 = 2x-0.5x

1.5x = -9

x = -9/1.5

x = -6 .
Confirmed by jeifunk [12/22/2014 2:34:47 AM], Rated good by jeifunk

27,363,110
*
Get answers from Weegy and a team of really smart live experts.
Popular Conversations
A universal truth is one that readers A. realize is archaic and ...
Weegy: A universal truth is one that readers accept as a fact in some cases but not others.
Time-outs are ineffective because? A. an adult uses a ...
Weegy: Time-outs are ineffective because a power struggle is created between the adult and the child. User: ...
S
L
Points 1219 [Total 1530] Ratings 14 Comments 1079 Invitations 0 Offline
S
L
R
P
R
P
R
P
R
Points 451 [Total 1226] Ratings 3 Comments 391 Invitations 3 Offline
S
R
L
R
P
R
P
R
R
R
R
Points 426 [Total 1310] Ratings 3 Comments 306 Invitations 9 Offline
S
L
P
P
P
Points 356 [Total 1232] Ratings 0 Comments 356 Invitations 0 Offline
S
L
R
Points 72 [Total 189] Ratings 0 Comments 72 Invitations 0 Online
S
Points 33 [Total 33] Ratings 1 Comments 23 Invitations 0 Offline
S
Points 23 [Total 23] Ratings 0 Comments 23 Invitations 0 Offline
S
Points 10 [Total 10] Ratings 0 Comments 0 Invitations 1 Offline
S
L
1
R
Points 2 [Total 1453] Ratings 0 Comments 2 Invitations 0 Offline
S
Points 2 [Total 2] Ratings 0 Comments 2 Invitations 0 Offline
* Excludes moderators and previous
winners (Include)
Home | Contact | Blog | About | Terms | Privacy | © Purple Inc.